Application of analytic hierarchy process to evaluate design criteria for humane trap cage. - Paramasivam, Sivajothi; Munisamy, Hari Krishnan; Rayappan, Santhansamy (Journal of Modern Manufacturing Systems and Technology, 2020)
Atrocities against stray animal’s especially large number of scavenging street dogs have increased at an alarming rate nationwide. Relevant authorities, in view of controlling stray animal population and curb chronic infections mulled cracking down on stray dogs using inhumane methods such as usage of tranquilizers or forcefully capturing. Thus, causing injuries, trauma and potentially death to these captured strays. Even though statistics about the number of violent incidents against strays remains unknown but animal welfare groups report constant complaints regarding animal cruelty. Animal activists mooted a request to design and built a modernize efficient yet low cost trap cage with a provision of technology which are normally ignored by many quarters; as a vehicle to educate the public on humane and compassionate ways to treat stray animals. The design of the cage involves consists of 3 parts, which was electronics hardware, communication system and critically the structure hardware whereby to withstand the possible aggressiveness of the animal. The objective of this paper is to present and apply the techniques of the analytic hierarchy process (AHP) in the prioritization and selection of design criteria of the trap cage. The finding shows that out of 5 design criteria, quality criteria is the most important criteria in designing of a humane trap cage issue. This is followed by innovativeness, cost, safety and aesthetics factors.